Quantifying the externalities of renewable energy plants using wellbeing data: The case of biogas - Christian Krekel; Julia Rechlitz; Johannes Rode; Alexander Zerrahn (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Although there is strong support for renewable energy plants, they are often met with local resistance. We quantify the externalities of renewable energy plants using well-being data. We focus on the example of biogas, one of the most frequently deployed technologies besides wind and solar. To this end, we combine longitudinal household data with novel panel data on more than 13, 000 installations in Germany. Identification rests on a spatial difference-in-differences design exploiting exact geographical coordinates of households, biogas installations and wind direction and intensity. We find limited evidence for negative externalities: impacts are moderate in size and spatially confined to a radius of 2, 000 metres around plants. We discuss implications for research and regional planning, in particular minimum setback distances and potential monetary compensations.
Keywords: C23; Q42; Q51; R20; 330; Renewables; Biogas; Externalities; Social Acceptance; Wellbeing; Spatial Analysis